NITROGEN , MOLYBDENUM AND INOCULATE ON COMMON BEANS - VIEIRA, Sandra Mara; RONZELLI JÚNIOR, Pedro; DAROS, Edelclaiton; KOEHLER, Henrique Soares; PREVEDELLO, Beatriz Monte Serrat (Scientia Agraria, 2000)
The objective of this study was to evaluate the effects, isolated or associated, of nitrogen (N), molybdenum (Mo) and inoculate on common beans yield and its components. The experiments were carried out in the field, over an Oxisol, in Pinhais, PR, with two varieties of common beans (Carioca and IAPAR 31), and two rates (with and without) respectively of N, Mo and inoculate, comprising a factorial, with four replications per treatment distributed on a complete randomized block experimental design. The inoculate was applied on the seeds following industry recommendations; N rate (40 kg ha-1) was applied over the soil surface, in a single application, thirty days after emergence, and at this time Mo (16,5 g ha-1) was sprayed on the plant leaves. All plots received 90 kg ha-1 of P2O5 and 30 kg ha-1 of K2O plowed into the soil before seeding. Results with significant differences were found with IAPAR 31 variety that had the yield positively and significantly affected by the triple interaction (N, Mo and inoculate) but N the greatest effect on it. The N also affected the number of pods per plant and were not seen any isolated influence of Mo or inoculate.